(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Dentigerous cyst develops around impacted, unerupted or developing teeth. It is often asymptomatic. However, it can be large and cause symptoms related to expansion. Painless swelling is the main symptoms, may be painful if infected. It can be found incidentally on dental radiography. Our patient is a 15 years old girl with painless swelling in right cheek with nasal obstruction. Diagnosis was confirmed by CT scan and needle aspiration. Under general anaesthesia enucleation of the cyst with removal of unerupted teeth was performed by Caldwell- Luc procedure. Post operative period was uneventful. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17637 Bangladesh J Otorhinolaryngol 2013; 19(2): 130-134